Cancer Cachexia - Prevalence and Predictors in Treatment-naive Patients - O'DONOGHUE, NIAMH CATHERINE (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2020)
Title: Cancer Cachexia Prevalence and Predictors in Treatment-naïve Patients Candidate Name: Dr Niamh O Donoghue Background Cancer cachexia is a common wasting syndrome, yet it remains poorly understood and under-recognised. Early recognition is essential to reduce and/or avoid its negative consequences. Management is challenging and currently there is no accepted standard of care. Despite an exponential increase in research in this area in recent years, studies investigating prevalence of cachexia in treatment-naive patients, particularly with gynaecological cancer, are limited. This thesis reports the prevalence of cancer cachexia in treatment-naïve patients and explores the impact cachexia may have on patients longitudinally. Oncology healthcare professionals perceptions of cachexia and its impact on patients were also investigated. Methods A number methodologies were employed in this thesis to investigate cachexia in treatment-naïve patients. These included a retrospective study of a large dataset in a mixed tumour population to establish prevalence of weight change and predictors of overall survival; a systematic review of the literature to estimate prevalence of cachexia in treatment-naïve gynaecological cancer patients; a prospective, exploratory study to determine prevalence and predictors of cachexia in a treatment-naïve gynaecological cancer cohort and a survey investigating the familiarity of Irish oncology healthcare professionals with cancer cachexia and its sequelae. Results Cachexia is prevalent in treatment-naïve cancer patients, despite the majority being overweight and/or obese at diagnosis. Using internationally recognised diagnostic criteria, prevalence in treatment-naïve gynaecological cancer patients was 21.8%. Poor understanding of cachexia and its associated burden may be a limitation for healthcare professionals in both recognition and management of patients with cachexia. Conclusions Cancer cachexia is prevalent in treatment-naïve patients, including gynaecological cancer patients. It leads to considerable patient burden and poorer prognosis for patients when compared to patients without cachexia. All healthcare professionals working in oncology have a duty to screen cancer patients for cachexia, however, an absence of nutritional education across disciplines has made this challenging. A comprehensive weight history, including nutritional symptoms, body composition analysis and monitoring of markers of systemic inflammation are necessary at all clinical encounters but especially at first assessment if those patients most at-risk are to be identified.
APPROVED